Evaluation of the mechanical properties of acetic-cure silicone with the addition of magnesium silicate - Ronald Vargas Orellana; Neide Pena Coto; Igor Studart Medeiros; Reinaldo Brito Dias (Universidade Estadual de Maringá, 2015)
Current study evaluates the mechanical properties (tensile and tear strength) of an acetic-cure silicone with the addition of 10 or 20% vol. magnesium silicate. Magnesium silicate was added to the silicone at concentrations of 10 (MS-10) and 20% (MS-20) volume, followed by the analysis of tensile strength, maximal elongation during tensile and tear strength. Results were compared to control group of silicone without additives (CG). Mean rates were determined and compared by analysis of variance and Tukey's test (p < 0.05). Control group had the greatest elongation when subjected to tensile strength (650%), whereas the MS-10 group statistically showed a better tensile strength (8.8 MPa) when compared to CG (7.5 MPa) and MS-20 (7.5 MPa) groups. Both magnesium silicate groups exhibited statistically similar tear strength, whereas MS-20 group demonstrated statistically greater tear strength. The addition of 10% magnesium silicate increased tensile strength, but tear strength and elongation were similar to control. The addition of 20% magnesium silicate did not affect tensile but increased tear strength.